A Model Driven Approach for Modeling and Generating PHP CodeIgniter based Applications - Arrhioui, Karim; Mbarki, Samir; Betari, Oualid; Roubi, Sarra; Erramdani, Mohammed (Transactions on Engineering and Computing Sciences, 2017)
During the last decade, web development industry has grown exponentially. Models have been introduced as a solution to face the challenge of both business and technology changes. In this article, we present a Model Driven based approach concerning the design of CodeIgniter based web applications. We describe a meta model of this framework and we also specify a set of transformations to generate the application’s source code taking into account the MVC (Model-View-Controller) architecture of CodeIgniter. In this approach, the PHP framework meta model is considered as a platform Specific model (PSM). Its instances are used as inputs to generate the source code through transformation rules carried out by Acceleo. This proposal is validated through the use of our approach to generate CRUD (Create, Read, Update and Delete) applications.